Education on the Benefits of Ethanol Extract Gel Preparation from Kelakai Leaves as a Burn Wound Treatment in Pantai Labu District - Syarifuddin, Aminah; Syahfitri, Wilda Dani; Suyudi, Yayuk Rahayu (JURNAL PENGMAS KESTRA (JPK), 2025)
Skin care is essential to protect the skin from damage, which can be achieved through healthy dietary intake and the direct application of topical products. The wound healing process plays a vital role in restoring tissue integrity and normal function. This process occurs in several phases, namely inflammation, proliferation, and maturation. The leaves of the kelakai plant have been utilized as the active ingredient in topical gel formulations due to their perceived safety and effectiveness. A gel formulation with a 15% w/w concentration has been proven to be the most effective, capable of reducing burn wound area by up to 13.75%, particularly in severe burn cases. These findings indicate the strong potential of kelakai leaf extract gel as an alternative treatment for burn injuries. A community service activity (PkM) involving 97 residents of Pantai Labu District was conducted with the aim of increasing public awareness regarding the proper and safe selection of topical medications. Participants were educated on the benefits, safety, and stability of the kelakai leaf extract gel, including the importance of appropriate pH levels that are compatible with human skin. Post-activity assessments revealed an increase in participants’ knowledge by 50% and 30% based on pre-test and post-test results, respectively, indicating the success of the program in enhancing understanding of plant-based topical gels as an alternative burn treatment. The PkM team also encouraged participants to be more selective and cautious when using similar products. This educational initiative successfully improved public knowledge regarding the use of medicinal plants as herbal remedies for burn wounds.